2020
DOI: 10.1029/2019ms002033
|View full text |Cite
|
Sign up to set email alerts
|

Increased Climate Response and Earth System Sensitivity From CCSM4 to CESM2 in Mid‐Pliocene Simulations

Abstract: Three new equilibrium mid‐Pliocene (MP) simulations are implemented with the Community Climate System Model version 4 (CCSM4) and Community Earth System Model versions 1.2 (CESM1.2) and 2 (CESM2). All simulations are carried out with the same boundary and forcing conditions following the protocol of Pliocene Model Intercomparison Project Phase 2 (PlioMIP2). These simulations reveal amplified MP climate change relative to the preindustrial going from CCSM4 to CESM2, seen in global and polar averages of surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 89 publications
0
48
0
Order By: Relevance
“…Previous modeling studies suggest that incorporating shrub/savanna vegetation over the Sahara as well as soil feedbacks in CCSM/CESM are important for the northward extension of the African monsoon during the Holocene (Levis et al, 2004; Thompson et al, 2019). Replacement of tundra with boreal forests over the NH high‐latitude continents, as indicated by pollen and macrofossil data (Figure 14), amplifies high‐latitude warming in CCSM/CESM simulations (Feng et al, 2020; Swann et al, 2010). In addition, a new optional feature in the CESM land model is the demographically structured dynamic vegetation model (Functionally Assembled Terrestrial Ecosystem Simulator), which will allow prediction of biome boundaries directly from plant physiological traits (Fisher et al, 2019; Lawrence et al, 2019).…”
Section: Summary and Discussionmentioning
confidence: 93%
“…Previous modeling studies suggest that incorporating shrub/savanna vegetation over the Sahara as well as soil feedbacks in CCSM/CESM are important for the northward extension of the African monsoon during the Holocene (Levis et al, 2004; Thompson et al, 2019). Replacement of tundra with boreal forests over the NH high‐latitude continents, as indicated by pollen and macrofossil data (Figure 14), amplifies high‐latitude warming in CCSM/CESM simulations (Feng et al, 2020; Swann et al, 2010). In addition, a new optional feature in the CESM land model is the demographically structured dynamic vegetation model (Functionally Assembled Terrestrial Ecosystem Simulator), which will allow prediction of biome boundaries directly from plant physiological traits (Fisher et al, 2019; Lawrence et al, 2019).…”
Section: Summary and Discussionmentioning
confidence: 93%
“…Pollen assemblages from marine sediments have been used in Panitz et al (2016) to reconstruct fluctuations of cool temperate and boreal conditions in northern Norway between 3.6 and 3.14 Ma. Plant macrofossils preserved in sediments across the Canadian Arctic Archipelago (Fletcher et al, 2017) have shown warmer and wetter conditions up to the mid-Pliocene in that region.…”
Section: Introductionmentioning
confidence: 99%
“…Each model's climate sensitivity also influences the simulated mid-Pliocene warming in PlioMIP2. For example, relative to CCSM4 and CESM1.2, CESM2 has the largest equilibrium climate sensitivity (Feng et al, 2020;Haywood et al, 2020) and simulates the strongest North https://doi.org/10.5194/cp-2020-120 Preprint. Discussion started: 22 September 2020 c Author(s) 2020.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…In this study, we analyze simulations with the fifteen models that have participated and provided the simulated AMOC results to PlioMIP2 (Table 1). They are CCSM4 (Feng et al, 2020), CCSM4-UoT (Chandan and Peltier, 2017;, CCSM4-Utrecht (Baatsen et al 2020, in prep), CESM1.2 (Feng et al, 2020), CESM2 (Feng et al, 2020), COSMOS , EC-Earth3-LR (Döscher et al, 2020, in prep), GISS-E2-1-G, HadCM3 (Hunter et al, 2019), IPSLCM5A2 (Tan et al, 2020), IPSLCM5A , IPSLCM6A-LR (Lurton et al, 2020), MIROC4m (Chan and Abe-Ouchi, 2020), NorESM1-F (Li et al, 2020), and NorESM-L (Li et al, 2020). All fifteen models have performed simulations according to the PlioMIP2 experimental protocol .…”
Section: Introduction Of Models Used In Pliomip2mentioning
confidence: 99%
See 1 more Smart Citation